Group Counseling with Behavioral Approach Using Modeling Technique on Aggressive Behavior of Students Influenced by Seniority Culture in Islamic Boarding Schools - Khoirul Abdul Majid; Ika Ariyati; Kus Hendar; Kurnia Azizah (Grief and Trauma, 2025)
Aggressive behavior among students in Islamic boarding schools influenced by seniority culture has become a serious problem requiring systematic intervention. This study aims to examine the effectiveness of group counseling using a behavioral approach with modeling technique in reducing aggressive behavior among students at Walisongo Islamic Boarding School. A quasi-experimental method with a Nonequivalent Control Group Pretest-Posttest design was employed. Twenty male students from Sunan Kalijogo dormitory identified as having aggressive behavior tendencies were selected through purposive sampling based on the Buss Aggression Scale screening. The sample was divided into an experimental group (n = 10) and a control group (n = 10). The experimental group received four behavioral group counseling sessions using modeling technique, each lasting 45 minutes, while the control group received no treatment. Data were analyzed using IBM SPSS Statistics 25 with Shapiro-Wilk normality test, Levene's Test for homogeneity, paired-sample t-test, and independent-sample t-test with Welch's correction. Results showed a significant decrease in aggressive behavior scores after the intervention (t(19) = -19.965, p < 0.001), with a pretest mean of 60.45 (SD = 7.13) and posttest mean of 96.75 (SD = 3.14). These findings confirm that behavioral group counseling with modeling technique is effective in reducing aggressive behavior among students influenced by seniority culture.